Association of Lipid Profile with Non-Alcoholic Fatty Liver Disease diagnosed on Ultrasound - Ambreen Zahoor, Iram Iqbal, Sajid Naseem, Zaidan Idrees Choudhary, Ambreen Zahoor, Iram Iqbal, Sajid Naseem, Zaidan Idrees Choudhary (Journal of Rawalpindi Medical College, 2020)
Objectives: To evaluate lipid profile parameters in patients with various grades of non-alcoholic fatty liver disease (NAFLD) diagnosed on sonography. Material and Method: This descriptive cross-sectional study was conducted at HBS General Hospital, Islamabad over a period of six months from January 2018 to June 2018. Seventy-nine adults of either gender diagnosed with NAFLD on ultrasonography were consecutively included. Fasting blood sample of all the subjects was analyzed for total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C) Comparison of lipid abnormalities between different grades of NAFLD was done by statistical analysis with p-value <0.05 considered statistically significant. Results: Out of the total 79 patients, grade I, II, and III NAFLD was diagnosed in 56.6%, 45.5%, and 3.9% respectively. Total cholesterol (TC), triglycerides (TG), low density lipoprotein cholesterol (LDL-C) were raised in 28 (35.4%), 43 (54.4%) and 43 (54.4%) patients respectively. Low serum high-density lipoprotein cholesterol (HDL-C) levels were seen in 74 (93.6%) of patients. Statistical analysis showed a significant increase in frequency as well as mean values in all serum lipid profile parameters with the severity of NAFLD grades except total cholesterol (TC). Conclusion: Increasing grades of NAFLD showed a significant correlation with higher levels of cholesterol, LDL, and decreasing levels of HDL, which are all associated with cardiovascular problems.